2015
DOI: 10.1039/c4cc06197g
|View full text |Cite
|
Sign up to set email alerts
|

ESR spectroscopy as a powerful tool for probing the quality of conjugated polymers designed for photovoltaic applications

Abstract: Here we report the application of the Electron Spin Resonance (ESR) spectroscopy as a highly sensitive analytical technique for assessment of the electronic quality of organic semiconductor materials, particularly conjugated polymers. It has been shown that different batches of the same conjugated polymer might contain substantially different amounts of radical species which were attributed to structural defects and/or impurities behaving as traps for mobile charge carriers. Good correlations between the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…The formation of long‐lived free‐radical species in polymer films is also suggested as the source of voltage loss. One study indicates a negative correlation between the concentration of free‐radical species in commercially purchased polymers and initial BHJ V OC . Electron spin resonance measurements of neat OPV polymer films illuminated under inert conditions shows an increase in free‐radical concentration over illumination time ( Figure ) .…”
Section: Intrinsic Degradationmentioning
confidence: 99%
“…The formation of long‐lived free‐radical species in polymer films is also suggested as the source of voltage loss. One study indicates a negative correlation between the concentration of free‐radical species in commercially purchased polymers and initial BHJ V OC . Electron spin resonance measurements of neat OPV polymer films illuminated under inert conditions shows an increase in free‐radical concentration over illumination time ( Figure ) .…”
Section: Intrinsic Degradationmentioning
confidence: 99%
“…We have shown previously that such radical species behave as deep 65 traps for mobile charge carriers and affect severely the performance of different conjugated polymers in organic solar cells. 12 Therefore, continuous illumination of polymer samples is expected to result in accumulation of radical species and degradation of their photovoltaic properties. 70 To investigated the photostability of conjugated polymers ( Fig.…”
Section: Organic Solar Cells Relative Stability Of Materials Can Be mentioning
confidence: 99%
“…Different samples of the same polymer might differ by the molecular weight, amount of defects and residual impurities, and consequentially, different polymer batches might perform quite differently in OPV devices. 12 To resolve this limitation an extensive experimental program with a wide international cooperation is currently planned. 13 Recently, Troshin et al suggested that Electron Paramagnetic Resonance (EPR) spectroscopy is a very powerful tool for assessment of the quality of different conjugated polymers used as the electron donor in OPV 12 and monitoring their photochemical and thermal degradation.…”
Section: Introductionmentioning
confidence: 99%